2023
DOI: 10.3389/fpsyg.2023.1210672
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception of coronavirus disease 2019 and career adaptability among college students: the mediating effect of hope and sense of mastery

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has not only caused widespread economic recession but also had a serious negative impact on the employment of college students. However, little is known about the relationship and mechanisms between the risk perception of COVID-19 and career adaptability. This study aimed to examine whether the risk perception of COVID-19 is associated with career adaptability directly and indirectly through hope and a sense of mastery in college students. A questionnaire survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This suggests that hope is an important mechanism mediating psychological adjustment (Cohen and Wills, 1985 ; Hagen et al, 2010 ). In this ever-changing world, hopeful individuals tend to have higher levels of career wellbeing (e.g., job satisfaction and career adaptability) to prepare for a successful life (Hirschi, 2014 ; Ding and Li, 2023 ). Yalçin and Malkoç ( 2015 ) found that meaning in life positively predicted hope among college students.…”
Section: Meaning In Life Hope and Career Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that hope is an important mechanism mediating psychological adjustment (Cohen and Wills, 1985 ; Hagen et al, 2010 ). In this ever-changing world, hopeful individuals tend to have higher levels of career wellbeing (e.g., job satisfaction and career adaptability) to prepare for a successful life (Hirschi, 2014 ; Ding and Li, 2023 ). Yalçin and Malkoç ( 2015 ) found that meaning in life positively predicted hope among college students.…”
Section: Meaning In Life Hope and Career Adaptabilitymentioning
confidence: 99%
“…The key to career preparation for college students is improving their career adaptability, which is regarded as a core ability for career success (Hou et al, 2012 ). Research has shown that high levels of career adaptability can cushion the impact of environmental stressors, which in turn enhances wellbeing (Ding and Li, 2023 ). Therefore, it is necessary to investigate the factors influencing career adaptability to help students grow under the stress of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, the inherent risks of medical profession became apparent, leading to a reevaluation of commitment versus personal safety. 14 , 15 This dichotomy has posed challenges and introspection for many contemplating a journey to medicine and has manifest the profound and multifaceted aftershocks of the COVID-19 pandemic. As the next generation of medical professionals shape their path, these repercussions will likely influence the structure of global healthcare for years to come.…”
Section: Introductionmentioning
confidence: 99%